Cholesterol-sensing role of phenylalanine in the interaction of human islet amyloid polypeptide with lipid bilayers1. Issue 71 (5th December 2018) - Hao, Ruijie; Li, Yang; Guan, Liping; Lu, Tong; Meng, Feihong; Wang, Chunyu; Li, Fei
Abstract : The interaction of hIAPP with cholesterol in the membrane is mediated by Phe15. Abstract : The interactions between hIAPP and the pancreatic β-cells are associated with β-cell death in type II diabetes. Cholesterol modulates hIAPP-membrane interaction and hIAPP aggregation. The molecular mechanism underlying this is not well understood. Here we explore the cholesterol-sensing role of F15 in the interactions of hIAPP and hIAPP1–19 with various compositions of lipids, including DOPC, DPPC and DOPC/DPPC using NMR, CD, ThT fluorescence and dye leakage assays. We show that both hIAPP and hIAPP1–19 are more potent in the disruption to the membranes with cholesterol than they are in the disruption to the membranes without cholesterol. A substitution of F15 by leucine affects the binding and disruption of the peptides to the membranes slightly in the absence of cholesterol, but decreases the activities largely in the presence of cholesterol. F15 also plays a role in accelerating fibrillar assembly of hIAPP, but the function is independent of cholesterol in nature. The promotion of cholesterol to the disruptive potency of hIAPP is more effective in the membrane with raft-like domains than in the membrane with a dispersed distribution of cholesterol. Our results suggest that F15 plays a key role in the cholesterol-sensing binding and disruption of hIAPP to the PC membranes and the distribution of cholesterol in the membranes has an influence on the disruptive activity of hIAPP.